Pre-feasibility study for the establishment of a hectare of passion fruit in San Pablo Turrubares - Flores Peralta, Jorge (2019)
With this pre-feasibility study, the aim is to know the economic viability of a passion fruit production system in the San Pablo de Turrubares area, which has the optimum soil and climate conditions for the development and production of this crop, considering the commercialization of the fruit in the wholesale market CENADA. It also aims to generate knowledge about a non-traditional product in the primary sector of the Costa Rican economy, promoting rural development. This is positive because interested producers can study this report to learn about the profitability of the crop in terms of marketing opportunities to encourage national agricultural diversification through non-traditional products. The evaluation period for the project is 7 years because by this date two complete cycles of the crop will have been obtained, which will allow knowing in the medium term if it is profitable or not. In addition, the costs in which the organization must incur, payment for tax and labor obligations, investments and necessary reinvestments, as well as the income that the activity generates are presented. For this, technical, socioeconomic and political, organizational and legal, financial and market studies are developed. At the end of the evaluation period, a NPV of ₡ 1,073,470 and an IRR of 20.42% were obtained, at a capital cost rate of 19.05%.